The impact of creativity on creative performance among university students in higher vocational education in China: The mediating role of autonomous motivation - LianLian Ji; Yuan-Cheng Chang (Journal of Pedagogical Research, 2024)
This study aims to explore whether the creativity of university students in Higher Vocational Education in China can enhance their creative performance through autonomous motivation. The theoretical foundation of this study is interactionist model of creativity, the study employs structural equation modeling for analysis and validation. A survey assessing creativity, creative performance, and autonomous motivation was administered to students from higher vocational schools in China, yielding a valid sample of 392. The overall model results indicate that the creativity of vocational college students has a significant positive impact on creative performance, creativity positively predicted autonomous motivation, which enhanced creative performance. The autonomous motivation partially mediates the relationship between creativity and creative performance. The findings recommend that higher vocational institutions initiate creative activities to foster students' creativity and continuously bolster their autonomous motivation, thus enhancing the creative performance of future technical and skilled professionals - vocational college students.